STUDENTS PERSPECTIVE TOWARD THE USE OF WHATSAPP APPLICATION ON WRITING SKILL - Thie thien Dewi Kartika Sari; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
This research was aimed at described the students perspective toward the use of WhatsApp application in online learning class especially at teaching writing in the VIII B class students of SMP N 2 Kradenan in 2019/2020 Academic Year. This research was used a Descriptive Qualitative Research as a method. The research was the VIII-B students of SMP N 2 Keradenan in 2019/2020 academic year. In collecting the data, the researcher used two method, that can be mention as interview, questionnaire. To analysis the data, the researcher used qualitative data analysis and likert scale. The qualitative data analysis method that was used proposed about the aim of this method were to get information about existing conditions and have been already used in educational research, to describe what is exist with respect to variable or condition in some situation we can use qualitative method. The results of the research show that WhatsApp application can improve the students’ writing skill. The students get interest when the teacher used WhatsApp application as a media at their online learning. It can be proofed by the percentage used likert scale with the topic: the students feel interest with the media (86.67%), writing skill is increase while using WhatsApp application (60.00%). It can be conclude that through WhatsApp application the students gather their interest in learning writing English and they can improve their writing skill.   Keywords: Descriptive Qualitative, Writing Skill, Online Learning, WhatsApp Application